(untitled) (The Peerian Journal, 2025)
This article explores the development of stage expressiveness in primary school children during pop singing training. Special attention is paid to the psychological characteristics of this age group, pedagogical strategies, and methodological techniques that contribute to the development of artistic abilities. The article is supported by practical examples from teaching experience in children’s music schools and includes references to the works of Russian scholars in the field of music education